Digitalisasi Sistem Recording Bank Pakan Ternak untuk Manajemen Risiko pada Peternakan Integrated Farm Jonggol, Jawa Barat - Nadya Khairunnisa; Dina Angelina; Dinda Raudhatul Jannah (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
Ruminant farming plays a significant role in food provision and the economy through the livestock and related agribusiness sectors. One of the major challenges in livestock management is efficient feed management. Poor feed management can lead to various problems such as nutritional deficiencies, diarrhea, and poisoning in livestock, which ultimately result in losses. Skillage Integrated Farm, a livestock business unit of SMK Skill Village Islamic School, faces challenges in feed recordkeeping and management. This research aims to develop a digital feed bank recording system at Skillage Integrated Farm to improve feed management efficiency and reduce the risk of losses. This study uses a qualitative approach with data collection through interviews, observations, and discussions. The findings indicate that the implementation of this digital system improves record accuracy, facilitates feed consumption evaluation, and supports data-driven decision-making. Additionally, the system reduces operational costs and enhances the sustainability of the farm business.